Lightweight heavy-duty CNC horizontal lathe based on particle damping materials. (15th January 2021) - Xiao, Wangqiang; Xu, Zhanhao; Bian, Hechuan; Li, Zhongkai
Graphical abstract: Highlights: A method of machine tool lightweight is proposed based on particle damping. A particle parameter optimization method based on energy dissipation is established. The vibration of lightweight machine tools is reduced. Abstract: With the development of high-precision, high-speed, and green computer numerical controlled (CNC) machine tools, the advantages of lightweight versions of such tools are becoming increasingly obvious. Taking a ZN-XK2840 CNC lathe as an example, in this study a lightweight design method is proposed for CNC machine tools based on particle damping technology. The static performance of conventional CNC machine tools is analyzed using a finite element method, and the wall thickness is optimized. Then, the dynamic characteristics of conventional CNC machine tools, such as the modal characteristics and harmonic response, are analyzed. The particle damping technology can effectively reduce the vibration of the machine structure in the vibration transmission path. In this paper, the discrete element dynamic method is used for the finite element model of a lathe. Based on a traditional machine tool, the dynamic characteristics of the machine tool structure with a particle damper are analyzed. The lathe with a particle damper is manufactured according to the lightweight design. The acceleration and displacement amplitudes of lightweight machine tools are smaller than those of traditional machine tools. The third-order natural frequency of lightweight CNC machine bed is increased by about 28.49%, and the vibration amplitude of harmonic response is reduced by 3.38%. Compared with the similar machine tools used in industry, the light CNC lathe with particle damper reduces the weight by 50.8% on average.